Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/mp.12296
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative contrast‐enhanced spectral mammography based on photon‐counting detectors: A feasibility study

Abstract: Purpose To investigate the feasibility of accurate quantification of iodine mass thickness in contrast-enhanced spectral mammography. Materials and Methods A computer simulation model was developed to evaluate the performance of a photon-counting spectral mammography system in the application of contrast-enhanced spectral mammography. A figure-of-merit (FOM), which was defined as the decomposed iodine signal-to-noise ratio (SNR) with respect to the square root of the mean glandular dose (MGD), was chosen to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…In the FE image, the position of the sagittal slice is marked by a dashed line. ml) 19,22,50 and conventional breast CT (2 mg/ml) using energy-integrating detectors. 51 The VNC image provides additional information that can serve as a reliable substitute for a native CT image, making it possible to avoid an additional CT scan.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the FE image, the position of the sagittal slice is marked by a dashed line. ml) 19,22,50 and conventional breast CT (2 mg/ml) using energy-integrating detectors. 51 The VNC image provides additional information that can serve as a reliable substitute for a native CT image, making it possible to avoid an additional CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Using photon‐counting technology in a whole‐body CT, it has been demonstrated that the performance is comparable to conventional dual‐source CT scanners 33 . Investigations on CEM with a photon‐counting detector and DE subtraction also showed promising results 11,19,22 . High energy (HE) and low energy (LE) images are acquired simultaneously from a single x‐ray exposure and are used to perform DE subtraction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spectroscopic x‐ray imaging detectors are under development in academic and industry laboratories. Advantages of spectroscopic detectors over energy‐integrating detectors include improved dose efficiency and the potential for single‐exposure, material‐specific imaging …”
Section: Introductionmentioning
confidence: 99%